2020
DOI: 10.21608/aimj.2020.29538.1219
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 14-3-3η protein and Muskelosketal ultrasound in early rheumatoid arthritis patients.

Abstract: Background: Despite recent advances in treatment, Rheumatoid arthritis (RA) remains a significant cause of morbidity and premature mortality. 14-3-3η protein was found at higher levels of serum and synovial fluid of patients with arthritis. Aim of work: to assess serum levels of 14-3-3η protein in early rheumatoid arthritis and correlate it with the disease activity and ultrasound findings. Patient and Methods: Thirty naïve patients with early RA were subjected for thorough clinical examination, labratory inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…On the other hand, Dammona et al [26] found that although serum 14-3-3η protein level was significantly higher in RA than controls and serum 14-3-3η protein was significantly correlated with serum RF and anti-CCP, the protein did not show significant correlations parameters of disease activity including ESR, CRP, DAS28 or musculoskeletal ultrasound parameters. The discrepancy between the findings of that study and ours can be attributed to the lower sample size and type of RA patients enrolled in that study (that study enrolled 30 patients with early RA).…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, Dammona et al [26] found that although serum 14-3-3η protein level was significantly higher in RA than controls and serum 14-3-3η protein was significantly correlated with serum RF and anti-CCP, the protein did not show significant correlations parameters of disease activity including ESR, CRP, DAS28 or musculoskeletal ultrasound parameters. The discrepancy between the findings of that study and ours can be attributed to the lower sample size and type of RA patients enrolled in that study (that study enrolled 30 patients with early RA).…”
Section: Discussionmentioning
confidence: 92%